PERLINDUNGAN HUKUM KONSUMEN DALAM TRANSAKSI SECARA ONLINE - Sukarmi, Sukarmi; Permono, Yudhi Tri (Jurnal Hukum, 2019)
he purpose of this study are to know the process of online sale and purchase transactions and to find out the problem in online sale transaction and settelment efforts.The approach method used in this research is the normative juridical approach, meaning that legal research is done by examining library materials or secondary data. Data analysis method used is qualitative analysis. From the results of this study it can be concluded 1) the process of buying and selling transactions online (Site Lazada.co.id) include: entry to the site / web shop online, choose the type of goods desired, click the purchase order, make payment transactions, the merchant to send goods 2) problems in online buying and selling transactions and the settlement efforts such as the weakness of the consumer position against the business actors, the validity of the agreement pursuant to Article 1320 Civil Code and no guarantor institution on line. Efforts through the granting of trust by business actors in the website, the consumer can know the business actor is a provider of electronic transactions that can be trusted. The government should increase awareness of consumers to want to report losses due to online transactions